2008
DOI: 10.1063/1.2822439
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural origin of switching field distribution in patterned Co∕Pd multilayer nanodots

Abstract: Microstructure and magnetic properties of a Co/Pd multilayer on a controlled Pd/Si seed layer for double-layered perpendicular magnetic recording media

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
57
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(62 citation statements)
references
References 22 publications
3
57
0
1
Order By: Relevance
“…As a consequence, the larger the number of ͑100͒ and ͑110͒ grains per dot is, the lower is the switching field. 7,8 Note that the reversal fields of the BPM dots are systematically lower than the effective anisotropy, even before irradiation ͓Fig. 3͑a͔͒.…”
Section: -mentioning
confidence: 99%
See 2 more Smart Citations
“…As a consequence, the larger the number of ͑100͒ and ͑110͒ grains per dot is, the lower is the switching field. 7,8 Note that the reversal fields of the BPM dots are systematically lower than the effective anisotropy, even before irradiation ͓Fig. 3͑a͔͒.…”
Section: -mentioning
confidence: 99%
“…3,4 The SFD has multiple origins but intrinsic growth defects leading to anisotropy distribution has been shown to be a dominant one. [5][6][7][8] These defects include misorientated grains, grain boundaries, distribution of easy axis angle, variations in lattice stress, and variations in thicknesses or interface roughness in multilayers. Two recent investigations 7,8 indicate that misorientated crystalline grains are the major microstructural origin of SFD in ͑111͒ textured ͓Co/Pd͔ multilayers.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Variations in island reversal fields are assumed to be induced by variations of the magnitude or direction of the local anisotropy, such as originating from island size, shape, composition, and (crystalline) structure as well as localized strain, corrupted island edges, or misaligned grains. [3][4][5][6][7] In a recent study, Lau et al found that islands with a low switching field (easy switchers) do predominantly contain a "trigger" grain larger than the exchange length with in-plane [100] vector, whereas islands with high switching field (stubborn or hard switchers) do not. 7 The magnetic nanodots in Ref.…”
mentioning
confidence: 99%
“…[3][4][5][6][7] In a recent study, Lau et al found that islands with a low switching field (easy switchers) do predominantly contain a "trigger" grain larger than the exchange length with in-plane [100] vector, whereas islands with high switching field (stubborn or hard switchers) do not. 7 The magnetic nanodots in Ref. 7 were fabricated by transferring an island array hard mask defined via electron-beam lithography into a continuous Co/Pd multilayer film using Ar sputter etching.…”
mentioning
confidence: 99%